2019
DOI: 10.1186/s12947-019-0181-z
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter MitraClip repair alters mitral annular geometry – device induced annular remodeling on three-dimensional echocardiography predicts therapeutic response

Abstract: BackgroundEchocardiography (echo) is widely used to guide therapeutic decision-making for patients being considered for MitraClip. Relative utility of two- (2D) and three-dimensional (3D) echo predictors of MitraClip response, and impact of MitraClip on mitral annular geometry, are uncertain.MethodsThe study population comprised patients with advanced (> moderate) MR undergoing MitraClip. Mitral annular geometry was quantified on pre-procedural 2D transthoracic echocardiography (TTE) and intra-procedural 3D tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 21 publications
(28 reference statements)
0
12
0
Order By: Relevance
“…Previous studies have already suggested that AP diameter at baseline, 28 post‐procedural reduction in AP diameter 7 and ventricular chamber size 33 might be possible determinants of MitraClip effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have already suggested that AP diameter at baseline, 28 post‐procedural reduction in AP diameter 7 and ventricular chamber size 33 might be possible determinants of MitraClip effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al used 3D TEE to measure TEER-induced changes in annular geometry. They confirmed that suboptimal response (residual MR grade >mild) was associated with larger pre-procedural MA area on 3D TEE, and found that the magnitude of reductions in MA circumference by intra-procedural 3D TEE was greater among patients with, compared to those without, suboptimal response on follow-up TTE ( 124 ).…”
Section: Percutaneous Treatment Of Mitral Valve Prolapsementioning
confidence: 86%
“…Furthermore, the authors did not find an association between change in annular measurements and degree of mitral regurgitation reduced [24]. Conversely, Kim et al [25] found that the magnitude of reduction in annular circumference was greater among patients with suboptimal MitraClip response (>mild mitral regurgitation) at 2.7 AE 2.5 months follow-up (P ¼ 0.017). Otherwise, their results were consistent with others, reinforcing that MitraClip significantly reduced annular area, circumference and anterior-posterior diameter (all P < 0.001) acutely [25].…”
Section: Key Pointsmentioning
confidence: 88%
“…Conversely, Kim et al [25] found that the magnitude of reduction in annular circumference was greater among patients with suboptimal MitraClip response (>mild mitral regurgitation) at 2.7 AE 2.5 months follow-up (P ¼ 0.017). Otherwise, their results were consistent with others, reinforcing that MitraClip significantly reduced annular area, circumference and anterior-posterior diameter (all P < 0.001) acutely [25]. Most recently, Caballero et al validated model of functional mitral regurgitation.…”
Section: Key Pointsmentioning
confidence: 94%